Strengthening of existing stone arch bridges using UHPC: Theoretical analysis and case study. (September 2022) - Wang, Zongshan; Yang, Jun; Zhou, Jianting; Yan, Kebang; Zhang, Zhongya; Zou, Yang
Abstract: Ultrahigh-performance concrete (UHPC) is widely used in retrofitting damaged structures, but few studies on the reinforcement of stone arch bridges have been reported. This paper presents a simplified analysis and its application for a damaged stone arch bridge. The finite strength of the masonry, the friction and rotation between voussoirs and the bond shear strength between UHPC and stone were considered. A double-sided shear test was carried out to determine the bond shear strength where stones were taken from the considered bridge. Four UHPC strengthening configurations, including intrados, extrados, U-hoop (wrapping for three sides) and □-hoop (wrapping for four sides) reinforcement configurations were discussed. The collapse mechanisms and load collapse multipliers were analyzed in their original and strengthened configurations. The analyses performed indicate that the interface strategies of scabbling and post-installed rebar can ensure ductility and interface bonding strength. The considered non-reinforced bridge shows a lack of load-carrying capacity of approximately 40% with respect to that required by the demand of local heavy traffic. To obtain load collapse multiplier values greater than one, the respective thicknesses of the UHPC reinforcement layer required by the four UHPC reinforcement configurations are 10 cm, 8.3 cm, 6.8 cm and 6.0 cm. The structural stiffness and carrying capacity have been significantly improved after reinforcement, which shows that UHPC is reliable for reinforcing a stone arch bridge and offers the value of popularization and application.